Outcome of Antiviral Immunity in the Liver Is Shaped by the Level of Antigen Expressed in Infected Hepatocytes. Issue 6 (27th September 2018) - Manske, Katrin; Kallin, Nina; König, Verena; Schneider, Annika; Kurz, Sandra; Bosch, Miriam; Welz, Meike; Cheng, Ru‐Lin; Bengsch, Bertram; Steiger, Katja; Protzer, Ulrike; Thimme, Robert; et al.
Abstract : The liver bears unique immune properties that support both immune tolerance and immunity, but the mechanisms responsible for clearance versus persistence of virus‐infected hepatocytes remain unclear. Here, we dissect the factors determining the outcome of antiviral immunity using recombinant adenoviruses that reflect the hepatropism and hepatrophism of hepatitis viruses. We generated replication‐deficient adenoviruses with equimolar expression of ovalbumin, luciferase, and green fluorescent protein driven by a strong ubiquitous cytomegalovirus (CMV) promoter (Ad‐CMV‐GOL) or by 100‐fold weaker, yet hepatocyte‐specific, transthyretin (TTR) promoter (Ad‐TTR‐GOL). Using in vivo bioluminescence to quantitatively and dynamically image luciferase activity, we demonstrated that Ad‐TTR‐GOL infection always persists, whereas Ad‐CMV‐GOL infection is always cleared, independent of the number of infected hepatocytes. Failure to clear Ad‐TTR‐GOL infection involved mechanisms acting during initiation as well as execution of antigen‐specific immunity. First, hepatocyte‐restricted antigen expression led to delayed and curtailed T‐cell expansion—10, 000‐fold after Ad‐CMV‐GOL versus 150‐fold after Ad‐TTR‐GOL‐infection. Second, CD8 T‐cells primed toward antigens selectively expressed by hepatocytes showed high PD‐1/Tim‐3/LAG‐3/CTLA‐4/CD160 expression levels similar to that seen in chronic hepatitis B. Third, Ad‐TTR‐GOL but not Ad‐CMV‐GOL‐infected hepatocytes escaped being killed by effector T‐cells while still inducing high PD‐1/Tim‐3/LAG‐3/CTLA‐4/CD160 expression, indicating different thresholds of T‐cell receptor signaling relevant for triggering effector functions compared with exhaustion. Conclusion: Our study identifies deficits in the generation of CD8 T‐cell immunity toward hepatocyte‐expressed antigens and escape of infected hepatocytes expressing low viral antigen levels from effector T‐cell killing as independent factors promoting viral persistence. This highlights the importance of addressing both the restauration of CD8 T‐cell dysfunction and overcoming local hurdles of effector T‐cell function to eliminate virus‐infected hepatocytes.